Preparation method of conductive corrosion-resistant modified layer of stainless steel bipolar plate of PEM water electrolyser
By laser cladding using FeCoNiCrAl high entropy alloy powder on the stainless steel bipolar plate of the PEM water electrolytic cell, a high conductive and high corrosion-resistant coating with a thickness of no less than 70-80μm was prepared, and the film layer thin in the prior art was solved. The problems of high cost and complex process meet the performance requirements of actual working conditions.
Patent Information
- Application Number
- CN202411417463.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
The surface modified film layer of stainless steel bipolar plates for existing PEM water electrolytic cells is thin, the bonding strength is not high, the cost is high, the preparation process is complicated, and it is difficult to meet the requirements of high conductivity, corrosion resistance and hydrogen embrittlement resistance in actual working conditions.
The high-entropy alloy coating is prepared on the surface of the 316L stainless steel bipolar plate substrate by using FeCoNiCrAl high-entropy alloy powder-feeding laser cladding process, with a thickness of no less than 70-80μm, avoid the use of precious metals, and optimize laser cladding. Process parameters to improve conductivity and corrosion resistance.
Achieve high-conductive and high corrosion-resistant coatings with a large thickness, reduce costs, simplify process flow, and improve the bonding strength between film bases. It is suitable for complex working conditions of PEM water electrolytic cells, with high energy density and small Heat-affected zone, wide application range.
Smart Images

Figure CN119287418A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by water electrolysis, and in particular to a method for preparing a conductive and corrosion-resistant modified layer of a stainless steel bipolar plate of a PEM water electrolyzer. Background Art
[0002] As one of the main components of PEM water electrolyzer, bipolar plate not only plays the role of supporting membrane electrode and diffusion layer, but also is an important channel for converging gas (hydrogen and oxygen) and conducting electrons. It also occupies about 80% of the weight and 40-50% of the cost of the electrolyzer. Compared with graphite and composite bipolar plates, metal bipolar plates have higher strength, better formability, impact resistance and lower permeability, and are widely used in PEM electrolyzers. At present, the mainstream metal bipolar plates of PEM (proton exchange membrane) electrolyzers are usually titanium-based bipolar plates, with precious metal coatings such as Pt or Au or other surface treatments on the surface. The cost is high and the coating is relatively thin, which is very unfavorable to reducing the cost of bipolar plates, expanding industrial applications and increasing service life. Bipolar plates are repeated in large quantities in PEM electrolyzers, so the price of precious metal coatings has a greater impact on the cost of PEM electrolyzers. Precious metals such as platinum, titanium, and iridium have become the main bottlenecks for the expansion of PEM electrolyzers. Reducing the use rate of precious metals or developing alternative materials is the future development trend of PEM electrolyzers to reduce costs. In addition, compared with titanium-based metal bipolar plates, stainless steel bipolar plates have more cost advantages and have received increasing attention in recent years. In order to ensure the long-term durability of stainless steel bipolar plates, it is necessary to modify their surface so that their surface has excellent electrical conductivity and low interface contact resistance.
[0003] At present, the research related to stainless steel metal bipolar plates is mostly applied to the fuel cell industry, while stainless steel metal bipolar plates for PEM water electrolyzers are rarely seen, and most of them are restricted by the preparation process, resulting in a thin surface modification layer (usually <70μm), which is extremely unfavorable for improving the practicality and service life of stainless steel bipolar plates for PEM water electrolyzers. In recent years, with the development of the green hydrogen industry, the research related to the surface modification of stainless steel bipolar plates for PEM water electrolyzers has attracted more and more attention. For example, patent CN115992363A discloses a surface modification method for bipolar plates for water electrolysis hydrogen production, that is, depositing a conductive material on the surface of a titanium or stainless steel substrate by electrophoretic deposition, and then decomposing and carbonizing the stabilizer by sintering to obtain a CN / conductive material composite coating, which has a simple and efficient process, low cost, and a wide range of applications; however, there are disadvantages such as low production efficiency and limited electrophoretic deposition thickness (10 to 40μm). Patent CN118147675A discloses a stainless steel bipolar plate for a PEM water electrolyzer, which is subjected to a zoned coating treatment, thereby reducing the metal coating area and effectively reducing the material cost. However, the mass fraction of precious metals in the mixed coating is 8% to 15%, and the cost is still relatively high. Patent CN117165940A discloses a stainless steel bipolar plate, wherein the stainless steel surface is mechanically polished and ultrasonically cleaned, then nickel-plated, and then graphene is grown in situ on the nickel-plated stainless steel surface using chemical vapor deposition technology; Patent CN114875464A discloses a PEM electrolyzer anode bipolar plate, wherein Ni and Ni-Cr composite layers are electroplated on the surface of a stainless steel substrate, and then a slurry consisting of conductive carbon black and epoxy resin is attached, followed by curing, carbonization and alloying to form a gradient coating; these methods also have the disadvantages of complex preparation process flow, difficult control, thin film layer, and low bonding strength between the membrane and the substrate. Laser cladding technology can achieve strong bonding between membranes and substrates - metallurgical bonding. Patent CN117535712A uses stainless steel as the substrate. On the surface of the substrate, an iron alloy base layer, a transition layer containing iron alloy elements and precious metal elements, and a precious metal surface layer are sequentially formed by laser cladding, forming a bipolar plate with a three-layer coating structure. It can be used for surface modification of stainless steel bipolar plates for PEM water electrolyzers. However, the transition layer and the surface layer contain 18-30wt% platinum and 45-60wt% platinum, respectively. Obviously, the use of precious metals is still relatively large, and there is no material cost advantage.
[0004] In summary, the relevant research on the surface modification of stainless steel bipolar plates for PEM water electrolyzers has made certain progress, but the surface modification membrane layer of most stainless steel bipolar plates for PEM water electrolyzers is relatively thin, some are even less than 1μm, and the bonding strength between the membrane and the substrate is not high. This is extremely unfavorable for improving the practicality and service life of stainless steel bipolar plates for PEM water electrolyzers. In addition, for the actual working conditions of bipolar plates in PEM water electrolyzers, in addition to having high conductivity and corrosion resistance, stainless steel bipolar plates should also meet the following requirements: the cathode side has high resistance to hydrogen embrittlement, and the anode side has high corrosion resistance in an oxygen-rich strong acid environment at a potential of about 2V. Summary of the invention
[0005] In order to solve the problems of high cost, complex preparation process, thin coating thickness and so on in the prior art and meet the requirements of actual working conditions, the present invention discloses a laser cladding preparation method for a high-conductivity, high-corrosion-resistant high-entropy alloy coating on the surface of a 316L stainless steel bipolar plate of a PEM (proton exchange membrane) water electrolyzer. The present invention uses FeCoNiCrAl (equimolar ratio) high-entropy alloy powder as feed material and adopts a coaxial powder feeding laser cladding process to deposit a high-entropy alloy coating on the surface of a sandblasted 316L stainless steel plate substrate. The coating is prepared without using precious metals, which reduces the cost. The purpose is to provide a relatively thick (thickness not less than 70-80 μm) high-bonding, high-conductivity and high-corrosion-resistant coating that is not suitable for the surface of a 316L stainless steel bipolar plate of a PEM water electrolyzer.
[0006] The technical means adopted by the present invention are as follows:
[0007] A method for preparing a conductive and corrosion-resistant modified layer of a stainless steel bipolar plate of a PEM water electrolyzer, specifically comprising the following steps:
[0008] Step 1, using a pressurized sandblasting machine to perform dry sandblasting on the surface of the coating to be prepared of the 316L stainless steel bipolar plate substrate;
[0009] Step 2, ultrasonically cleaning the surface of the coating to be prepared on the sandblasted 316L stainless steel bipolar plate substrate, and drying for standby use;
[0010] Step 3: Load the dried 316L stainless steel bipolar plate substrate onto the welding tooling platform, put the FeCoNiCrAl high entropy alloy powder into the powder feeder, and prepare a high entropy alloy laser cladding coating on the surface of the coating to be prepared on the 316L stainless steel bipolar plate substrate by a laser cladding process.
[0011] Furthermore, the thickness of the 316L stainless steel bipolar plate substrate is 3.0 to 5.0 mm.
[0012] Furthermore, the thickness of the obtained high entropy alloy laser cladding coating is not less than 70-80 μm.
[0013] Furthermore, in step 3, the laser power of laser cladding is 800-1200 W, the scanning speed is 25-35 mm / s, and the powder feeding amount is 8-14 g / min.
[0014] Furthermore, the sandblasting in step 1 adopts dry sandblasting method, uses 36# white corundum sand particles, the spraying air pressure range is 0.3-0.6MPa, the spraying inclination angle is 60-90°, and the spraying distance is 100-150mm.
[0015] Furthermore, the ultrasonic cleaning in step 2 specifically includes: using acetone, ethanol and deionized water to perform ultrasonic cleaning for 15 to 30 minutes in sequence to remove dust and impurities on the surface of the coating to be prepared, and vacuum drying for standby use.
[0016] Furthermore, the specific process of optimizing the laser cladding process parameters in step 3 includes:
[0017] The laser cladding process parameters: laser power, scanning speed and powder feeding amount were taken as independent variables, and a three-factor three-level orthogonal table was used to plan the orthogonal experimental scheme for preparing high-entropy alloy laser cladding coatings. The performance evaluation indicators of the high-entropy alloy laser cladding coatings prepared by each orthogonal experimental scheme were collected: interface contact resistance ICR, self-corrosion current density I corr and self-corrosion potential E corr ;
[0018] According to the test results of the performance evaluation indicators corresponding to each orthogonal test scheme, the Taguchi method was used to perform signal-to-noise ratio analysis and grey correlation analysis to determine the optimal level of each laser cladding process parameter:
[0019] (1) The interface contact resistance ICR and self-corrosion current density I corr and self-corrosion potential E corr The signal-to-noise ratios are calculated as response indicators respectively, and the optimal level points of the laser cladding process parameters corresponding to each response indicator are determined through range analysis;
[0020] (2) The signal-to-noise ratio calculation results of the three response indicators are subjected to grey correlation analysis, and the three response indicators are transformed into a single response indicator. By calculating the grey correlation and range analysis, the influence order of each laser cladding process parameter on the grey correlation is obtained, and then the optimal level point of each laser cladding process parameter is determined.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. The method for preparing the conductive corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer provided by the present invention adopts FeCoNiCrAl high entropy alloy, and can prepare a high entropy alloy laser cladding coating with a coating thickness of not less than 70-80 μm on a 3.0-5.0 mm thick 316L stainless steel bipolar plate substrate; by utilizing the four major effects of the high entropy alloy, such as the "cocktail" effect, the coating has excellent conductivity and corrosion resistance, and avoids the use of precious metals to reduce costs. The technology has the advantages of high energy density, small heat-affected zone, wide application range, etc., and is easy to achieve large-scale and automated production.
[0023] 2. The method for preparing the conductive and corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer provided by the present invention only prepares the coating by laser cladding on the surface of the 316L stainless steel bipolar plate, and does not change the main body of the stainless steel plate, so it does not affect its mechanical strength.
[0024] 3. The method for preparing the conductive and corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer provided by the present invention has the advantages of mature technology, high processing efficiency, and continuous production, and can meet the performance requirements of the 316L stainless steel bipolar plate of the PEM (proton exchange membrane) water electrolyzer under complex working conditions of the battery stack.
[0025] Based on the above reasons, the present invention can be widely promoted in the field of hydrogen production by water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0027] Figure 1 It is the measured value (@1.5MPa) of the interface contact resistance ICR of the 1# to 10# coating samples (before corrosion) in Comparative Example 1 and Example 1.
[0028] Figure 2 To simulate the anode environment of PEM water electrolyzer (temperature 80℃, corrosive solution 0.5mol / L H2SO4+5PPM F - The comparison of the potentiodynamic polarization curves of the coating samples 1# to 10# in Comparative Example 1 and Example 1 under the conditions of solution, continuous air flow at a flow rate of 20 ml / min). DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention provides a method for preparing a conductive and corrosion-resistant modified layer of a stainless steel bipolar plate of a PEM water electrolyzer, which specifically comprises the following steps:
[0031] Step 1, using a pressurized sandblasting machine to perform dry sandblasting on the surface of the coating to be prepared of the 316L stainless steel bipolar plate substrate;
[0032] Step 2, ultrasonically cleaning the surface of the coating to be prepared on the sandblasted 316L stainless steel bipolar plate substrate, and drying for standby use;
[0033] Step 3: Load the dried 316L stainless steel bipolar plate substrate onto the welding tooling platform, put the FeCoNiCrAl high entropy alloy powder into the powder feeder, and prepare a high entropy alloy laser cladding coating on the surface of the coating to be prepared on the 316L stainless steel bipolar plate substrate by a laser cladding process.
[0034] Furthermore, the thickness of the 316L stainless steel bipolar plate substrate is 3.0 to 5.0 mm.
[0035] Furthermore, the thickness of the obtained high-entropy alloy laser cladding coating can be adjusted in a wide range, with the thinnest being no less than 70-80 μm and the thickest being up to 2-3 mm. The specific thickness can be achieved by adjusting the laser cladding process parameters as needed.
[0036] Furthermore, in step 3, the laser power of laser cladding is 800-1200 W, the scanning speed is 25-35 mm / s, and the powder feeding amount is 8-14 g / min.
[0037] Furthermore, the sandblasting in step 1 adopts dry sandblasting method, uses 36# white corundum sand particles, the spraying air pressure range is 0.3-0.6MPa, the spraying inclination angle is 60-90°, and the spraying distance is 100-150mm.
[0038] Furthermore, the ultrasonic cleaning in step 2 specifically includes: using acetone, ethanol and deionized water to perform ultrasonic cleaning for 15 to 30 minutes in sequence to remove dust and impurities on the surface of the coating to be prepared, and vacuum drying for standby use.
[0039] Furthermore, the specific process of optimizing the laser cladding process parameters in step 3 includes:
[0040] The laser cladding process parameters: laser power, scanning speed and powder feeding amount were taken as independent variables, and a three-factor three-level orthogonal table was used to plan the orthogonal experimental scheme for preparing high-entropy alloy laser cladding coatings. The performance evaluation indicators of the high-entropy alloy laser cladding coatings prepared by each orthogonal experimental scheme were collected: interface contact resistance ICR, self-corrosion current density I corr and self-corrosion potential E corr ;
[0041] According to the test results of the performance evaluation indicators corresponding to each orthogonal test scheme, the Taguchi method was used to perform signal-to-noise ratio analysis and grey correlation analysis to determine the optimal level of each laser cladding process parameter:
[0042] (1) The interface contact resistance ICR and self-corrosion current density I corr and self-corrosion potential E corr The signal-to-noise ratios are calculated as response indicators respectively, and the optimal level points of the laser cladding process parameters corresponding to each response indicator are determined through range analysis;
[0043] (2) The signal-to-noise ratio calculation results of the three response indicators are subjected to grey correlation analysis, and the three response indicators are transformed into a single response indicator. By calculating the grey correlation and range analysis, the influence order of each laser cladding process parameter on the grey correlation is obtained, and then the optimal level point of each laser cladding process parameter is determined.
[0044] The present invention adopts FeCoNiCrAl high entropy alloy powder and can prepare non-precious metal coatings through a laser cladding process, with low preparation cost and a higher thickness of the prepared coating compared with the prior art.
[0045] In the present invention, the surface of the 316L stainless steel plate substrate to be laser clad is sandblasted for pretreatment, the main purpose of which is to clean the substrate surface, increase the coating adhesion area, and prefabricate the surface compressive stress, thereby reducing the internal stress of the coating, preventing adverse reactions, enhancing the bonding force between the membrane and the substrate, and improving the durability of the bipolar plate; FeCoNiCrAl high entropy alloy powder is used as the coating raw material, the main purpose of which is to utilize the four major effects of the high entropy alloy, such as the "cocktail" effect, so that the coating takes into account both electrical conductivity and corrosion resistance, and avoids the use of precious metals to reduce costs; the coaxial powder feeding laser cladding technology is used to prepare the surface modification layer of the stainless steel bipolar plate, mainly based on the advantages of laser cladding with high energy density, small heat affected zone, dense crystal structure, wide application range, etc., and it is easy to achieve large-scale and automated production. Compared with other surface engineering technologies such as vapor deposition and thermal spraying, the laser cladding coating has a denser structure and a metallurgical bond between the membrane and the substrate. Therefore, this technology is more suitable for the preparation of high-bonding and high-corrosion-resistant functional coatings, and the thickness of the prepared coating is also larger.
[0046] Example 1
[0047] This embodiment adopts the method for preparing the conductive corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer described in the present invention, which specifically includes the following steps:
[0048] Step 1, using a pressurized sandblasting machine to perform dry sandblasting on the surface of the coating to be prepared of the 316L stainless steel bipolar plate substrate;
[0049] Step 2, ultrasonically cleaning the surface of the coating to be prepared on the sandblasted 316L stainless steel bipolar plate substrate, and drying for standby use;
[0050] Step 3, loading the dried 316L stainless steel bipolar plate substrate (in this embodiment, the thickness is 5.0 mm) onto the welding tooling platform, putting the FeCoNiCrAl high entropy alloy powder into the powder feeder, and preparing a high entropy alloy laser cladding coating on the surface of the coating to be prepared of the 316L stainless steel bipolar plate substrate by a laser cladding process;
[0051] The specific process of optimizing laser cladding process parameters in step 3 includes:
[0052] As shown in Table 1, a three-factor three-level orthogonal table was used to plan the laser cladding process parameters, and a total of nine groups of FeCoNiCrAl high entropy alloy laser cladding coating samples from 1# to 9# were prepared. In this embodiment: the three levels of laser power were 800W, 1000W, and 1200W; the three levels of scanning speed were 25mm / s, 30mm / s, and 35mm / s; the three levels of powder feeding were 8g / min, 12g / min, and 14g / min;
[0053] Table 1 Orthogonal table of three factors and three levels
[0054]
[0055] Taking the 316L stainless steel substrate without laser cladding surface modification as comparative example 1, according to the corresponding methods of "7.3.2 Contact resistance test" and "8 Bipolar plate material corrosion current density test" in GB / T20042.6-2011 "Proton exchange membrane fuel cell part 6: Bipolar plate characteristic test method", the interface contact resistance ICR of the surface of the laser cladding coating samples of comparative example 1 and 9 groups under different pressures (1.0-2.0MPa) (the measured value under 1.5MPa is taken for comparison) and the self-corrosion current density I under the dynamic potential polarization under the simulated anode environment of the PEM water electrolyzer (temperature 80℃, corrosive solution 0.5mol / L H2SO4+5PPM F_ solution, continuous air flow at a flow rate of 20ml / min) is tested respectively. corr and self-corrosion potential E corr , so as to characterize its electrical conductivity and corrosion resistance (the self-corrosion current density of the sample I corr and self-corrosion potential E corr is obtained by fitting through Tafel extrapolation method);
[0056] The test results of samples 1# to 9# in Table 1 are as follows: Figure 1 and Figure 2 As shown; the test results of comparative example 1 are: the interface contact resistance ICR of the stainless steel surface before corrosion is 48.80mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr 6.45μA·cm -2 and -270.90mV;
[0057] Comparing the performance evaluation indicators of samples 1# to 9# and comparative example 1, it can be seen that:
[0058] For coating 1# in Table 1, the main laser cladding process parameters are laser power 800W, scanning speed 25mm / s, powder feeding speed 8g / min; the interface contact resistance ICR before corrosion is 60.19mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr and 25.72 μA·cm -2 and -274.50mV; obviously, compared with Comparative Example 1, its conductivity and corrosion resistance are not as good as Comparative Example 1;
[0059] For coating 2# in Table 1, the main laser cladding process parameters are laser power 800W, scanning speed 30mm / s, powder feeding speed 14g / min; the interface contact resistance ICR before corrosion is 35.90mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr and 41.82 μA·cm -2 and -288.20mV; obviously, compared with Comparative Example 1, its conductivity is slightly better, but its corrosion resistance is far inferior to Comparative Example 1;
[0060] For coating 3# in Table 1, the main laser cladding process parameters are laser power 800W, scanning speed 35mm / s, powder feeding speed 12g / min; the interface contact resistance ICR before corrosion is 165.94mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr 31.25μA·cm -2 and -283.50mV; obviously, compared with Comparative Example 1, its corrosion resistance and conductivity are far inferior to Comparative Example 1;
[0061] For coating 4# in Table 1, the main laser cladding process parameters are laser power 1000W, scanning speed 25mm / s, powder feeding speed 14g / min; the interface contact resistance ICR before corrosion is 121.43mΩ·cm 2 @1.5Mpa; in the simulated PEM water electrolyzer anode environment, the self-corrosion current density Icorr and self-corrosion potential Ecorr were 18.40μA·cm -2 and -283.50mV; obviously its conductivity and corrosion resistance are far inferior to those of Comparative Example 1;
[0062] For coating 5# in Table 1, the main laser cladding process parameters are laser power 1000W, scanning speed 30mm / s, powder feeding speed 12g / min; the interface contact resistance ICR before corrosion is 105.40mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr and 27.43 μA·cm -2 and -282.80mV; obviously its conductivity and corrosion resistance are far inferior to those of Comparative Example 1;
[0063] For coating 6# in Table 1, the main laser cladding process parameters are laser power 1000W, scanning speed 35mm / s, powder feeding speed 8g / min; the interface contact resistance ICR before corrosion is 87.13mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr 0.85μA·cm -2 and -80.88mV; obviously, compared with Comparative Example 1, its corrosion resistance is much better, but its conductivity is not as good as Comparative Example 1;
[0064] For coating 7# in Table 1, the main laser cladding process parameters are laser power 1200W, scanning speed 25mm / s, powder feeding speed 12g / min; the interface contact resistance ICR before corrosion is 87.53mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr They are 11.93 μA·cm -2 and -283.20mV; obviously its conductivity and corrosion resistance are far inferior to those of Comparative Example 1;
[0065] For coating 8# in Table 1, the main laser cladding process parameters are laser power 1200W, scanning speed 30mm / s, powder feeding speed 8g / min; the interface contact resistance ICR before corrosion is 41.49mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr 17.05μA·cm -2 and -275.20mV; obviously, compared with Comparative Example 1, its conductivity is slightly better, but its corrosion resistance is far inferior to Comparative Example 1;
[0066] For coating 9# in Table 1, the main laser cladding process parameters are laser power 1200W, scanning speed 35mm / s, powder feeding speed 14g / min; the interface contact resistance ICR before corrosion is 47.63mΩ·cm 2 @1.5Mpa; simulated PEM water electrolyzer anode environment, the self-corrosion current density I during potentiodynamic polarization corr and self-corrosion potential E corr and 0.89 μA·cm -2 and -139.30mV; obviously, its conductivity and corrosion resistance are better than those of Comparative Example 1;
[0067] In this embodiment, according to the interface contact resistance ICR, self-corrosion current density I corr and self-corrosion potential E corr , the Taguchi method was used to perform signal-to-noise ratio analysis and grey correlation analysis, and the order of influence of each laser cladding process parameter on the grey correlation was obtained as follows: powder feeding amount > scanning speed > power, and the optimal level of each laser cladding process parameter was determined: laser power was 1200W, scanning speed was 35mm / s, and powder feeding amount was 8g / min, which are the parameters corresponding to sample 10# in Table 1;
[0068] In summary, this embodiment finally obtains the ideal coating 10# (ICR and I corr As small as possible, E corr As positive as possible), the main laser cladding process parameters are laser power 1200W, scanning speed 35mm / s, and powder feeding speed 8g / min, as shown in Table 1; the interface contact resistance ICR before and after corrosion is 38.23 and 49.64mΩ·cm respectively. 2 @1.5Mpa; the performance of the 10# coating prepared at the optimal level of each laser cladding process parameter determined in this embodiment is characterized:
[0069] The self-corrosion current density I during potentiodynamic polarization under simulated PEM water electrolyzer anode environment corr and self-corrosion potential E corr 0.47 μA·cm -2 and -0.32mV; Obviously, the conductivity and corrosion resistance of the high entropy alloy laser cladding coating prepared by using the optimal level points of the laser cladding process parameters determined in step 3 of the method of the present invention are much higher than those of comparative example 1 (the ICR of comparative example 1 before and after corrosion are 48.80 and 181.65mΩ·cm respectively). 2 @1.5MPa, potentiodynamic polarization I corr and E corr and 6.45 μA·cm -2 and -270.90mV), it is obvious that the conductivity and corrosion resistance of the laser cladding coating 10# prepared by the optimal process parameters are far better than those of the comparative example 1;
[0070] At the same time, the coating thickness of samples 1# to 10# is shown in Table 1. It can be seen that the method of the present invention can be used to prepare a coating with a thickness of not less than 70-80 μm, and the thinnest is more than 100 μm, indicating that the preparation method of the conductive corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer provided by the present invention can solve the technical problems of high cost, complex preparation process and thin coating thickness in the prior art, and, combined with the method for optimizing the laser cladding process parameters provided by the present invention, a laser cladding process parameter scheme with a coating thickness of not less than 70-80 μm and better performance evaluation indicators can be obtained.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a conductive and corrosion-resistant modified layer of a stainless steel bipolar plate of a PEM water electrolyzer, characterized in that: The specific steps include: Step 1, using a pressurized sandblasting machine to perform dry sandblasting on the surface of the coating to be prepared of the 316L stainless steel bipolar plate substrate; Step 2, ultrasonically cleaning the surface of the coating to be prepared on the sandblasted 316L stainless steel bipolar plate substrate, and drying for standby use; Step 3: Load the dried 316L stainless steel bipolar plate substrate onto the welding tooling platform, put the FeCoNiCrAl high entropy alloy powder into the powder feeder, and prepare a high entropy alloy laser cladding coating on the surface of the coating to be prepared on the 316L stainless steel bipolar plate substrate by a laser cladding process.
2. The method for preparing the conductive and corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer according to claim 1, characterized in that: The thickness of the 316L stainless steel bipolar plate substrate is 3.0 to 5.0 mm.
3. The method for preparing the conductive and corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer according to claim 1, characterized in that: The thickness of the obtained high entropy alloy laser cladding coating is not less than 70-80 μm.
4. The method for preparing the conductive and corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer according to claim 1, characterized in that: In step 3, the laser power of laser cladding is 800-1200 W, the scanning speed is 25-35 mm / s, and the powder feeding amount is 8-14 g / min.
5. The method for preparing the conductive and corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer according to claim 1, characterized in that: In step 1, the sandblasting treatment adopts dry sandblasting method, uses 36# white corundum sand particles, the spraying air pressure range is 0.3-0.6MPa, the spraying inclination angle is 60-90°, and the spraying distance is 100-150mm.
6. The method for preparing the conductive and corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer according to claim 1, characterized in that: The ultrasonic cleaning in step 2 specifically includes: using acetone, ethanol and deionized water to perform ultrasonic cleaning for 15 to 30 minutes in sequence to remove dust and impurities on the surface of the coating to be prepared, and vacuum drying for later use.
7. The method for preparing the conductive and corrosion-resistant modified layer of the stainless steel bipolar plate of the PEM water electrolyzer according to claim 1, characterized in that: The specific process of optimizing laser cladding process parameters in step 3 includes: The laser cladding process parameters: laser power, scanning speed and powder feeding amount were taken as independent variables, and a three-factor three-level orthogonal table was used to plan the orthogonal experimental scheme for preparing high-entropy alloy laser cladding coatings. The performance evaluation indicators of the high-entropy alloy laser cladding coatings prepared by each orthogonal experimental scheme were collected: interface contact resistance ICR, self-corrosion current density I corr and self-corrosion potential E corr ; According to the test results of the performance evaluation indicators corresponding to each orthogonal test scheme, the Taguchi method was used to perform signal-to-noise ratio analysis and grey correlation analysis to determine the optimal level of each laser cladding process parameter: (1) The interface contact resistance ICR and self-corrosion current density I corr and self-corrosion potential E corr The signal-to-noise ratios are calculated as response indicators respectively, and the optimal level points of the laser cladding process parameters corresponding to each response indicator are determined through range analysis; (2) The signal-to-noise ratio calculation results of the three response indicators are subjected to grey correlation analysis, and the three response indicators are transformed into a single response indicator. By calculating the grey correlation and range analysis, the influence order of each laser cladding process parameter on the grey correlation is obtained, and then the optimal level point of each laser cladding process parameter is determined.
Citation Information
Patent Citations
Method for preparing low-interface contact resistance coating on surface of stainless steel bipolar plate
CN117165940A
Bipolar plate and preparation method thereof, small electrolysis chamber and electrolytic bath
CN117535712A
Bipolar plate for PEM water electrolyser
CN118147675A
Cited By
Fuel cell bipolar plate aging life prediction method based on multi-temperature-zone correction
CN119471401A
Bipolar plate composite coating preparation method based on high-entropy alloy and conductive polymer
CN121204768A